Menggugat Stereotype Kepemimpinan Perempuan Perspektif Hukum Islam - Wulandari, Ulfah Yunita; F, Fatmawati; Sultan, Lomba (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the period before the arrival of Islam, it was known that women suffered greatly and lived in poverty, but after the introduction of Islam, it was able to change the discriminatory situation that occurred before and enable women to have a decent life equivalent to prosperity. male position. In this article we present an example of female leadership in Islamic law. This article aims to provide an understanding of the views that allow women to become leaders in a country with the same position as men. Using normative research methods or bibliographic legal research is used as a research method. The normative approach is used to study and analyze library materials or search for information identified with research materials as legally required materials related to the research materials being conducted.